Preliminary Analysis of the Glycolipid Profile in Secondary Brain Tumors. (22nd November 2022) - Serb, Alina-Florina; Novaconi, Cristina; Georgescu, Marius; Puiu, Maria; Dema, Alis; Onulov, Robert; Sisu, Eugen
Abstract : Glycosphingolipids (GSLs) play numerous roles in cellular processes, including cell proliferation, apoptosis, inflammation, and cell signaling. Alteration of the GSLs metabolism leads to the accumulation of particular species of GSLs, which can lead to various pathologies, including carcinogenesis and metastasis; in essence, all neoplasms are characterized by the synthesis and aberrant organization of GSLs expressed on the cell surface. Secondary brain tumors make up the majority of intracranial cancers and generally present an unfavorable prognosis. In the present work, a native GSL mixture extracted and purified from a secondary brain tumor with primary pulmonary origin was obtained through extraction and purification and analyzed by MALDI TOF mass spectrometry. Research in the field of lipidomics could offer new data for the understanding of brain tropism and metastatic pathways, by studying the glycolipid molecules involved in the process of metastasis in general and in the production of brain metastases in particular. This could shed new light on the pattern of lipid glycosylation in secondary brain tumors, with a great impact on the effectiveness of cancer therapies, which could be adapted to the specific molecular pattern of the tumor.